2009
DOI: 10.1037/a0013147
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of a decision aid for BRCA1/BRCA2 mutation carriers: Impact on measures of decision making and satisfaction.

Abstract: Objective Genetic testing is increasingly part of routine clinical care for women with a family history of breast cancer. Given their substantially elevated risk for breast cancer, BRCA1/BRCA2 mutation carriers must make the difficult decision whether or not to opt for risk reducing mastectomy. To help BRCA1/2 carriers make this decision, we developed a computer-based interactive decision aid which we tested against usual care in a randomized controlled trial. Design Following the completion of genetic couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
134
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 40 publications
(63 reference statements)
2
134
2
Order By: Relevance
“…Previous studies have found that interventions designed to facilitate SDM (such as decision aids) reduce decisional conflict [e.g. 29], although a recent review concluded that evidence of effectiveness is mixed [30]. In contrast, blocking behaviour, such as interrupting and monopolising, was associated with increased 16 decisional conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that interventions designed to facilitate SDM (such as decision aids) reduce decisional conflict [e.g. 29], although a recent review concluded that evidence of effectiveness is mixed [30]. In contrast, blocking behaviour, such as interrupting and monopolising, was associated with increased 16 decisional conflict.…”
Section: Discussionmentioning
confidence: 99%
“…In 6 studies, decision aids were sent to patients by mail. 20,23,26,[28][29][30] Patients in the control groups had received either care as usual or general patient education materials.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%
“…Although focus group participants did not indicate specific types of information they were interested in receiving about fertility, they believed it should be given by health care providers using a systematic approach. To our knowledge there are several websites and decision aids about genetic testing (8,9), assisted reproductive technology (10), and cancer risk for survivors (11,12), but none are designed specifically for preimplantation genetic diagnosis and fertility preservation for patients at risk for development of cancer (13).…”
mentioning
confidence: 99%